Classification and Milling Increase Fly Ash Pozzolanic Reactivity - Snellings, Ruben; Kazemi-Kamyab, Hadi; Nielsen, Peter; Van den Abeele, Liesbet (Frontiers in Built Environment, 2021)
Upcycling and reclaiming of low quality or stored coal combustion fly ashes enables to tap into a voluminous resource of supplementary cementitious materials for low-carbon blended cements. Low reactivity fly ashes are usually either too crystalline or too coarse. Beneficiation treatments for coarse fly ashes comprise size classification or milling processes to extract or produce fine size fractions of higher pozzolanic reactivity. This paper compares the effect of size classification and milling treatments on the reactivity of a siliceous fly ash. The chemical reactivity is assessed using the R3 heat release test method and consumption of portlandite in blended cements. Both test results are used to calculate the degree of reaction of the fly ashes over time in blended cement. The results demonstrate a strong effect of particle size on fly ash reactivity and degree of reaction. It is shown that increasing the inherent reactivity of fly ashes is an effective way of both accelerating compressive strength gain and enhancing late age strength.